SUPPORTING WOMEN, PROTECTING THEIR RIGHTS AND INTERESTS IS A PRIORITY IN THE STATE POLICY OF UZBEKISTAN - Nilufar Djuraeva, Nodira Babadjanova, Muslima Bazarova (International Journal of Advanced Science and Technology, 2020)
This article highlights that women have always played an active and prominent role in the development of society, since the issue of women's achievement at the level of state policy has changed in recent years since independence of Uzbekistan. It is argued that the state policy for caring for women contributes to their social activity.